RESPON MASYARAKAT DESA NGADIREJO TERHADAP KEGIATAN PENGABDIAN YANG DILAKSANAKAN AKADEMI MILITER - Indiarto Kusno Hadi; Aris Basuki; Suluh Usada Adi; Silitonga, Frangky; Natalina Kristiana; Sermatutar Muhamaad Raindra; Sermatutar Mohamad Irul ferdiyansyah (JURNAL MAHATVAVIRYA, 2024)
This research is motivated by the courage to improve the image of the army and build the unity of the army and the people, especially Akmil with the community in use Cadet Training Area. Given the success of Cadets in carrying out one of the exercises is determined by the comfort of the village community used for training. Therefore, the research emphasized on the response and expectations of the community to the service activities carried out by the Defense Administration program of the Military Academy. This study was conducted by qualitative method by conducting purposive interviews. The respondents who were observed consisted of community leaders, village heads, village officials and villagers. The results of this study first in general the public has a positive response. It is more influenced by motives or interests. In this condition, the community is very happy because the service activities carried out by the Military Academy are an effort to answer the problems faced by the Ngadirejo Village Community. Meanwhile, the poor response in the form of pessimistic state of the service carried out occurs because of the experience of the community so far, seeing that the service that has been carried out by other agencies there is no assistance and follow-up. The two expectations of the community towards the service dilasanakan by Prodi Akmil Defense Administration, among others: mentoring, training in the army or cadets and socialization about Akmil